Carbohydrate Mouth-Rinsing Improves Overtime Physical Performance in Male Ice Hockey Players During On-Ice Scrimmages - Nyman, Danielle L. E.; Gamble, Alexander S. D.; Bigg, Jessica L.; Boyd, Logan A.; Vanderheyden, Alexander J.; Spriet, Lawrence L. (Frontiers in Nutrition, 2022)
Purpose This randomized, double-blind, crossover study examined the effects of mouth-rinsing (MR) with a carbohydrate (CHO) vs. a placebo (PLA) solution on external and internal loads in hydrated ice hockey players during regulation and overtime (OT) periods of an on-ice scrimmage. Methods Twelve skilled male hockey players (22.6 [3.4] years, 178.9 [4.7] cm, 84.0 [6.5] kg) played three 20-min regulation periods and one 12-min OT period of small-sided 3-on-3 scrimmage. Skaters repeated 2 min shift and rest intervals. Participants mouth rinsed with 25 mL of CHO or PLA solution approximately every 10 min for a total of 7 rinses. A local positioning system (LPS) tracked external load variables including speed, distance, acceleration, and deceleration. Internal load was monitored with heart rate (HR) sensors and a rating of perceived exertion (RPE). Results During regulation play, both the conditions developed similar fatigue, with significantly decreased high-intensity distance, average speed and decelerations, and increased RPE, from period 1 to 2 and 3. In OT, CHO MR increased the distance skated at high-intensity (224 [77], 185 [66] m, p = 0.042), peak speed (24.6 [1.6], 23.7 [1.3] km·h−1, p = 0.016), number of sprints (1.9 [1.2], 1.2 [0.9], p = 0.011), and decreased distance skated at slow speed (300 [33], 336 [47], p = 0.034) vs. PLA MR. OT RPE was similar between the two conditions in spite of more work done in CHO MR. Conclusions CHO MR may be a valuable practice to protect against decrements in external load with increased playing time in ice hockey, and possibly allows athletes to perform more work relative to perceived levels of exertion.